Polacy promowani na uniwersytecie w Perugii w XVI i XVII wieku - Chachaj, Marian (Biuletyn Historii Wychowania, 2024)
The text presents the results of research carried out mainly in the files kept at the Archivio Storico degli Università degli Studi di Perugia. As a result, it was possible to establish that between 1575 and 1682, 39 Poles obtained 40 doctorates from the University of Perugia (Piotr Odorowski obtained two doctorates, in law and theology): 33 promotions were in law, two in canon law, and five in theology. Some of the degrees were awarded to individuals who had not studied longer in Perugia, and should be treated as honorary titles (Stanisław Reszka being a case in point). Prior to receiving their degrees in Perugia, most graduates studied at other universities: the largest number, at least 23, in Krakow; a few at the Vilnius Academy. Some studied at Jesuit colleges in Braniewo, Kalisz or Poznań. Single individuals took up studies at the universities of Frankfurt (Oder), Ingolstadt and Würzburg, and at the academy in Olomouc. For obvious raasons, most people studied in Italy (mainly in Rome and Padua) . Among those promoted, a large group were Catholic diocesan clergy; promotions of monks were rare (only two graduates were Discalced Carmelites). There were 24 graduates – representatives of the nobility, and 13 of the bourgeoisie; in two cases it was not possible to establish their social origin. Finally, let me stress the great importance of Perugia doctorates for the careers of the individuals promoted. Unfortunately, in most cases, the names of the professors whose lectures were listened to by newcomers from Poland remain unknown